Pengaruh Host Live Streaming terhadap Pembelian Spontan dengan Diskon sebagai Variabel Moderasi di Kalangan Remaja Desa Ajung Kecamatan Kalisat Kabupaten Jember - Wardinatus Salsabila; Sri Redjeki; Febrina Gerhani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze: (1) the effect of live streaming hosts on impulse buying; (2) the effect of discounts on impulse buying; and (3) the moderating role of discounts in the relationship between live streaming hosts and impulse buying among adolescent TikTok Shop users in Ajung Village. This research employed a quantitative approach with a causal associative design. The study population consisted of 1,247 adolescents aged 17–24 years in Ajung Village who actively use TikTok Shop. A sample of 110 respondents was selected using a purposive sampling technique. Data were collected through a questionnaire measured on a 4-point Likert scale. The data were analyzed using Moderated Regression Analysis (MRA). The results indicate that: (1) live streaming hosts have a positive and significant effect on impulse buying (β = 0.456; p = 0.000); (2) discounts have a positive and significant effect on impulse buying (β = 0.378; p = 0.000); and (3) discounts negatively moderate the effect of live streaming hosts on impulse buying (β = -0.017; p = 0.036), meaning that discounts weaken the relationship between live streaming hosts and impulse buying. These findings suggest that substantial discounts shift consumers’ shopping motivation from hedonic to utilitarian. Therefore, adolescents are encouraged to be more critical in their purchasing decisions, businesses should consider implementing moderate discount strategies, and future researchers are recommended to examine mediating variables such as positive emotions.